The Association Between Eating Quickly and Excessive Gestational Weight Gain - Eri Abe; Minatsu Kobayashi; Reiko Horikawa; Naho Morisaki; Hisako Tanaka; Haruhiko Sago; Kohei Ogawa; Takeo Fujiwara (Mary Ann Liebert, 2023)
Objectives: Maintaining an appropriate gestational weight gain (GWG) is essential for a safe pregnancy and delivery. This study aimed to determine the association between the habit of eating quickly and the risk of excessive GWG. Methods: We administered a questionnaire on eating habits to 1246 pregnant Japanese women in their second to third trimesters. We categorized the participants into three groups according to their answers to the question ?Do you eat quickly?? Group 1, ?always? or ?usually?; Group 2, ?sometimes?; and Group 3, ?rarely? or ?never.? We assessed GWG according to the ?The Optimal Weight Gain Chart? (Ministry of Health, Labor and Welfare, Japan), and those who exceeded the criteria were considered ?excessive.? Logistic regression analysis was performed with the risk of excess GWG as the dependent variable and quick food intake as the independent variable, to obtain relevant odds ratios (ORs) and 95% confidence intervals (CIs). Model 1 was unadjusted, and Model 2 was adjusted for age, prepregnancy body mass index, energy intake, mother's educational attainment, household income, exercise habits, and childbearing experience. Results: The OR (95% CI) for Groups 2 and 3 in Model 1, compared with Group 1, was 0.80 (0.62?1.05) and 0.61 (0.43?0.88), respectively (p for trend?=?0.047). In Model 2, the OR (95% CI) for Groups 2 and 3 were 0.73 (0.55?0.96) and 0.59 (0.40?0.86), respectively (p for trend?=?0.003). Conclusion: These results suggest that quick food ingestion increases the risk of excessive GWG.